Closing the Health Gaps for the Elderly : Promoting Health Equity and Social Inclusion in Thailand - World Bank Group (World Bank, Washington, DC, 2016)
Thailand has succeeded in expanding coverage of publicly-funded and publicly-managed health insurance schemes, following the introduction of universal health coverage policy in 2001. While Thailand’s achievement of universal health coverage (UC) is well noted, recent researches and studies have indicated that there are still gaps in health utilization and financial protection. A recent study by Thailand’s health insurance system research office (HISRO) shows that utilization of health services by patients of three main health insurance schemes combined increased markedly after age 45 for both outpatient care and in-patient care but later dropped during an advanced age. Utilization of out-patient care services decreases among patients who are over 75 years of age while that of in-patient care services decreases after 85 years of age. The objective of the study is to identify the gaps of accessing UC scheme’s care system by the elderly population, focusing on utilization and financial protection aspects. The team conducted small-scale area-based qualitative case studies, focusing on elderly UC members who live in selected urban and rural areas in four different geographical regions of Thailand - Central, North, Northeastern, and South. The analysis confirms that there are poor elderly people who still need to pay for the costs of out-patient and in-patient care services at publicly run health facilities.